The Sinemurian ammonites of the Lusitanian Basin (Portugal): an example of complex endemic evolutioin - Dommergues, J.-L.; Meister, C.; Rocha, R. B. (Departamento de Ciências da Terra, 2010)
Palaeodiversity 3: 59–87; Stuttgart 30 December 2010 This work synthesizes all of the observations since the late nineteenth century of the highly endemic Late Sinemurian (Obtusum Chronozone) ammonite faunas of the Lusitanian Basin. It is based mainly on recent abundant collections from the Penedo da Saudade section near São Pedro de Muel (Leiria, Portugal). This rich material (some eight species and four genera), collected bed by bed, allow us to propose an initial biostratigraphic, palaebiogeographic, evolutionary and taxonomic synthesis of these mostly endemic faunas. The genus Epophioceroides (Subgen. indet. A) asteroceroides n. sp. Ptycharietites (Ptycharietites) heterogenus n. sp. So far they have been found at São Pedro de Muel only. The only non-endemic ammonite, Asteroceras sp. indet., collected from the base of the fossiliferous sequence, suggests an age in the Obtusum Chronozone for the subsequent taxa. Most probably faunas belong to the Stellare Subchronozone but taxa from the highest fossiliferous levels may also belong to the Denotatus Subchronozone. The newly collected material requires the morphological range of the genus Ptycharietites to be extended to include late forms that become either clearly evolute (subserpenticone) such as Ptycharietites (Pompeckioceras) cf. onchocephalus or clearly involute (suboxycone) such as Ptycharietites (?Subgen. indet. B) sp. indet. A. In terms of ontogeny, paedomorphosis - a rare "size-based" heterochronic process among the Asteroceratinae subfamily - is shown to be of major importance throughout the evolution of the genus Ptycharietites. In palaeobiogeographic terms all endemic Late Sinemurian (Obtusum Chronozone) ammonite faunas (Ptycharietites and Epophioceroides n gen.) of the Lusitanian Basin remain poorly understood. While they suggest marked isolation of the Lusitanian Basin and perhaps also constraining environmental conditions during the Obtusum Chronozone, there is nothing to indicate whether other bains of the "Iberai-Newfoundland" conjugate ...